2023
DOI: 10.31662/jmaj.2022-0104
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenetic Mechanism for Moyamoya Vasculopathy Including a Possible Trigger Effect of Increased Flow Velocity

Abstract: Moyamoya disease (MMD), which commonly exhibits moyamoya vasculopathy characterized by chronic progressive steno-occlusive lesions in the circle of Willis with “moyamoya” collateral vessels, has been well known for its unique demographic and clinical features. Although the discovery of the susceptibility gene RNF213 for MMD revealed the factor for its predominance in East Asians, the mechanisms underlying other predominant conditions (females, children, young to middle-aged adults, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…On the contrary, hemodynamic stress may appropriately explain all the predominant features of vasculopathy. 75 Hemodynamic studies by transcranial Doppler revealed increased flow velocity in females, 76,77 children, 78,79 young to middle-aged adults, 80 and the anterior circulation. 79,81 In addition, a transcranial Doppler study on patients with MMD showed that angiographically nonstenotic, namely, unaffected, arteries in the anterior circulation had significantly higher velocities in patients with MMD than in age-matched controls, suggesting that flow velocity increases in patients with MMD as a premorbid condition.…”
Section: Consideration Of Causes and Triggers Of MMV Mmrsv And Rnf213...mentioning
confidence: 98%
“…On the contrary, hemodynamic stress may appropriately explain all the predominant features of vasculopathy. 75 Hemodynamic studies by transcranial Doppler revealed increased flow velocity in females, 76,77 children, 78,79 young to middle-aged adults, 80 and the anterior circulation. 79,81 In addition, a transcranial Doppler study on patients with MMD showed that angiographically nonstenotic, namely, unaffected, arteries in the anterior circulation had significantly higher velocities in patients with MMD than in age-matched controls, suggesting that flow velocity increases in patients with MMD as a premorbid condition.…”
Section: Consideration Of Causes and Triggers Of MMV Mmrsv And Rnf213...mentioning
confidence: 98%